SINDROMA CUSHING PADA KEHAMILAN - Yetti Hernaningsih; Sidarti Soehita (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2005)
A 32 years old woman, pregnant 24-25 weeks, was admitted to the hospital with complaints of weakness, 6 years amenorrhoe, bruises on the skin and hair loss. Physical examination showed full moon face, buffalo hump, striae lividae, and echymosis. She was diagnosed as Cushing Syndrome with possible etiology adrenal tumor based on laboratory results: glucose intolerance, hypokalemia, increament of plasma cortisol before and after dexamethason supression tests (1352 and 1297 nmol/l), also decreement of plasma ACTH (5 pg/ml). During 22 days hospitalization, the patient’s condition became worse (heart failure, sepsis and shock).